Ultrasound-Guided Erector Spinae Plane Block in Thoracolumbar Spinal Surgery: A Systematic Review and Meta-Analysis - Viderman, Dmitriy; Aubakirova, Mina; Umbetzhanov, Yerlan; Kulkaeva, Gulnara; Shalekenov, S. B.; Abdildin, Yerkin G. (Frontiers in Medicine, 2022)
Introduction Neurosurgical spinal surgeries such as micro- discectomy and complex fusion surgeries remain the leading causes of disability-adjusted life-year. Major spinal surgeries often result in severe postprocedural pain due to massive dissection of the underlying tissues. While opioids offer effective pain control, they frequently lead to side effects, such as post-operative nausea and vomiting, pruritus, constipation, and respiratory depression. ESPB was successfully used in spinal surgery as a component of a multimodal analgesic regimen and it eliminated the requirements for opioids. The primary purpose of this systematic review and meta-analysis was to compare post-operative opioid consumption between ESPB and placebo. Methods To conduct this systematic review, we used the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)” guidelines. We conducted a search for relevant articles available in the following databases: Google Scholar, PubMed, and the Cochrane Library published up to March 2022. Results The total morphine consumption within 24 h after surgery was lower in the ESPB group, the mean difference (in mg of morphine) with 95% CI is −9.27 (−11.63, −6.91). The pain intensity (0–10) at rest measured 24 h after surgery was lower in the ESPB group, the MD with 95% CI is −0.47 (−0.77, −0.17). The pain intensity during movement measured 24 h after surgery was lower in the ESPB group, the MD with 95% CI is −0.73 (−1.00, −0.47). Post-operative nausea and vomiting were significantly lower in the ESPB group, the risk ratio with 95% CI is 0.32 (0.19, 0.53). Conclusion Ultrasound-guided ESPB was superior to placebo in reducing post-operative opioid consumption, pain intensity, post-operative nausea and vomiting, and prolonging the time to first rescue analgesia. There were no ESPB-related serious complications reported.